Differential Response to Exercise in African Americans with High Levels of Inflammation - Kretzschmar, Jan (Ethn Dis, 2017)
PURPOSE: Systemic inflammation, measured by C-reactive protein (CRP), is an important risk factor for cardiovascular disease (CVD) and mortality. We investigated whether aerobic exercise training (AEXT) affects African Americans with high inflammation (HI) the same way it does African Americans with low inflammation (LI) in terms of CVD risk factors. METHODS: 23 African Americans with CRP levels <3 mg/L (LI) and 14 African Americans with CRP ≥3 mg/L (HI) underwent six months of AEXT. Participants were sedentary, non-diabetic, non-smoking, with clinical blood pressure <160/100 mm Hg, were non-hyperlipidemic, had no signs of cardiovascular, renal, or pulmonary disease, and were not on medication. Measures included CD62E+ endothelial microparticles (EMPs), a measure of early stage endothelial dysfunction, as well as lipid and glucose profile, aerobic fitness, body composition, and blood pressure. RESULTS: The LI group improved aerobic fitness by 10%, body mass index by 3%, and plasma triglycerides by 20%, with no change being observed in HI group for these variables. The HI group improved fasting plasma glucose levels by 10%, with no change occurring in the LI group. Both groups improved CD62E+ EMPs by 38% and 59% for the LI and HI group, respectively. CONCLUSIONS: A standard AEXT intervention differentially affected CVD risk factors among African Americans with high and low inflammation. This may indicate that, in African Americans with high inflammation, AEXT alone may not be enough to reap the same benefits as their low-inflammation peers in terms of CVD risk modification.